Deep gluteal space problems: piriformis syndrome, ischiofemoral impingement and sciatic nerve release - Carro, Luis Perez (Muscles Ligaments Tendons J, 2016)
BACKGROUND: Deep gluteal syndrome (DGS) is an underdiagnosed entity characterized by pain and/or dysesthesias in the buttock area, hip or posterior thigh and/or radicular pain due to a non-discogenic sciatic nerve entrapment in the subgluteal space. Multiple pathologies have been incorporated in this all-included “piriformis syndrome”, a term that has nothing to do with the presence of fibrous bands, obturator internus/gemellus syndrome, quadratus femoris/ischiofemoral pathology, hamstring conditions, gluteal disorders and orthopedic causes. METHODS: This article describes the subgluteal space anatomy, reviews known and new etiologies of DGS, and assesses the role of the radiologist and orthopaedic surgeons in the diagnosis, treatment and postoperative evaluation of sciatic nerve entrapments. CONCLUSION: DGS is an under-recognized and multifactorial pathology. The development of periarticular hip endoscopy has led to an understanding of the pathophysiological mechanisms underlying piriformis syndrome, which has supported its further classification. The whole sciatic nerve trajectory in the deep gluteal space can be addressed by an endoscopic surgical technique. Endoscopic decompression of the sciatic nerve appears useful in improving function and diminishing hip pain in sciatic nerve entrapments, but requires significant experience and familiarity with the gross and endoscopic anatomy. LEVEL OF EVIDENCE: IV.